Potensi Bakteri Pelarut Fosfat dan Bakteri Penghasil IAA Asal Tanah Gambut terhadap Perkecambahan Tanaman Jagung (Zea mays L.) - Anggita, Via; Khotimah, Siti; Rahmawati; Mukarlina (Universitas Negeri Semarang, 2024)
Phosphate solubilizing bacteria and IAA-producing bacteria are bacteria that can help plant growth through their use by increasing the availability of phosphate (P) in the soil and helping plants absorb nutrients in the soil. This study aims to determine the effect of phosphate solubilizing bacteria and IAA-producing bacteria isolated from peat soil on the germination of corn (Zea mays L.) plants grown on peat soil. This research was conducted from June to September 2023 with a completely randomized design (CRD). Testing the effect of phosphate-solubilizing and IAA-producing bacteria was carried out using the method of soaking seeds and watering bacterial suspensions on plants. The results showed that A5 treatment had a significant effect on the number of leaves parameter, with A5 treatment (Bacillus cereus PF12, P13 and PF16 + Pseudomonas stutzeriIAA1) producing a germination percentage (100%), the number of leaves (5.09 strands) while the parameters of plant height and root length showed that all treatments were not significantly different.